Generation Z and tax compliance: Insights into knowledge, sanctions, and technology adoption with risk preferences as a moderating variable - Apsari, Naila Sahda; Dewi, Rana Kusuma; Lindrianasari, Lindrianasari (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the effect of tax knowledge, tax sanctions, and technology adoption on tax compliance based on the perceptions of Generation Z, using risk preference as a moderating variable. A quantitative research design was employed, with a sample obtained through an online questionnaire distributed to 219 respondents who are taxpayers born between 1997 and 2012. The results indicate that tax knowledge and technology adoption positively influence tax compliance. Additionally, risk preference enhances the relationship between technology adoption and tax compliance. Conversely, tax sanctions do not significantly affect tax compliance, and risk preference does not strengthen the relationship between tax knowledge or sanctions and tax compliance. These findings suggest that improving tax literacy and leveraging technology can be effective strategies for increasing compliance. The study emphasizes the importance of tax compliance among Generation Z to support the sustainable optimization of state revenue. Furthermore, this research provides valuable insights for policymakers to design more effective strategies that encourage voluntary tax compliance, ultimately contributing to fiscal stability and national development.